Building concrete and preparation method thereof
By modifying the plastic particles and cooperating with pineapple leaf fibers and chitosan, a network structure is formed, which solves the problem of plastic particles floating and insufficient binding force in concrete, and improves the integrity and compressive strength of the concrete.
Patent Information
- Application Number
- CN202411587264.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-14
AI Technical Summary
When plastic particles are incorporated into concrete, the lightweight properties of the plastic lead to floating problems, resulting in structural inhomogeneity and mechanical properties degraded, and the interface bonding between the plastic and the concrete substrate is insufficient, limiting performance improvement.
By modifying the plastic particles with acetone and sodium hypochlorite, the surface becomes rough and cooperate with pineapple leaf fibers and chitosan to form a three-dimensional network structure, enhancing interface binding and crack resistance, and alleviating the floating problem.
It improves the integrity and compressive strength of concrete, enhances durability, and ensures the uniform distribution and effective role of plastic particles in concrete.
Smart Images

Figure BDA0005124581220000051 
Figure BDA0005124581220000061 
Figure BDA0005124581220000071
Abstract
Description
Technical Field
[0001] The present invention relates to the field of building materials, and more specifically, to a kind of building concrete and a preparation method thereof. Background Art
[0002] In the field of construction engineering, concrete is an indispensable building material, and the optimization of its performance has always been a hot topic in scientific research and engineering practice. Although traditional concrete has excellent performance in strength, durability and workability, its limitations are becoming increasingly prominent with the advancement of technology and the improvement of environmental protection requirements. In particular, when plastic particles are added to concrete to improve specific properties (such as reducing dead weight and improving thermal insulation), some inherent shortcomings of plastic itself have become problems that need to be solved urgently.
[0003] The use of plastic particles in concrete faces several major challenges. First, the lightweight nature of plastic makes it easy for it to float during the mixing and pouring of concrete, resulting in an uneven internal structure of the concrete, which in turn reduces its overall mechanical properties and reduces its compressive strength. This unevenness may also cause durability problems for concrete during use, such as accelerated crack expansion and increased water seepage.
[0004] Secondly, the interfacial bonding between plastic and concrete matrix is weak, which limits the effect of plastic particles on the performance of concrete. The plastic surface usually lacks functional groups that form strong chemical bonds with cement paste, making the interface transition zone between the two a weak link in concrete and easily becoming the starting point of stress concentration and damage.
[0005] In addition, the addition of plastic particles may also have an adverse effect on the working performance of concrete. For example, if the plastic particles are unevenly dispersed, it will further aggravate the internal heterogeneity of the concrete, resulting in a decrease in the performance of the concrete. The decrease in the performance of concrete will limit its promotion and use in the construction field. Summary of the invention
[0006] In order to solve the above problems, enable plastics to fully play their role in concrete and improve the performance of concrete, the present application provides a building concrete and a preparation method thereof.
[0007] In the first aspect, the present application provides a kind of building concrete, adopts the following technical scheme: A building concrete, comprising the following raw materials in parts by mass: 220-240 parts of cement, 690-715 parts of fine aggregate, 1050-1150 parts of coarse aggregate, 130-150 parts of water, 140-170 parts of mineral admixture, 5-10 parts of admixture, 10-30 parts of modified plastic particles, 5-10 parts of pineapple leaf fiber, and 1-5 parts of chitosan; The modified plastic particles are prepared by modifying plastic particles with acetone and sodium hypochlorite.
[0008] By adopting the above technical solution, acetone and sodium hypochlorite are used to further modify the plastic particles, so that the surface of the modified plastic particles is rougher and the structure of the plastic particles is changed, thereby improving the interface bonding effect with concrete, which is beneficial to the penetration and bonding of cement paste.
[0009] Modified plastic particles cooperate with pineapple leaf fibers and chitosan. Pineapple leaf fibers, with their long fiber form and excellent mechanical properties, can form a three-dimensional network structure in concrete. This network structure not only provides additional skeleton support for concrete, but also enhances the crack resistance and toughness of concrete. The modified plastic particles with special structures can be well attached to the network structure of pineapple leaf fibers, further enhancing the strength and stability of the network structure. Chitosan, with its good film-forming properties and biocompatibility, can be used as an adhesive or surfactant to promote the close bonding between the network structure and the concrete matrix, effectively improving the integrity of the concrete, and improving its strength and durability. Moreover, since the modified plastic particles are attached to the pineapple leaf fibers and are "sealed and fixed" by chitosan film formation, the problem of traditional plastics easily floating can be further effectively alleviated.
[0010] When concrete is under pressure, the stable and strong network structure can quickly disperse the stress and alleviate the damage to the concrete caused by the pressure. On the other hand, since the floating problem of plastic is alleviated, its attached network structure is dispersed throughout the concrete system. When under pressure, the modified plastic particles can exert their own good deformation effect and further enhance the compressive strength of the concrete.
[0011] Preferably, in terms of weight percentage, the modified plastic particles are 15-25 parts, the pineapple leaf fibers are 6.5-8 parts, and the chitosan is 1.5-3.5 parts.
[0012] By adopting the above technical scheme, the dosage and coordination of modified plastic particles, pineapple leaf fibers and chitosan in the system are further limited, so that the coordination among the three is more sufficient, the distribution is more uniform, and the network structure is stronger, thereby further improving the performance of concrete.
[0013] Preferably, the method for preparing the modified plastic particles comprises the following steps: Step a: soaking the plastic particles in an acetone solution, taking them out and drying them to obtain once-soaked plastic particles; Step b: soaking the once soaked plastic particles in a sodium hypochlorite solution with a mass concentration of 5-10% for 1-2 hours, and the mass ratio of the once soaked plastic particles to the sodium hypochlorite solution is 1:(2-5); taking out and drying to obtain modified plastic particles.
[0014] Preferably, the acetone solution is a mixture of acetone and water in a volume ratio of (3-5):1.
[0015] Preferably, the mass ratio of the plastic particles to the acetone solution is 1:(5-10).
[0016] Preferably, in step a, the plastic particles are soaked in the acetone solution for 1-2 hours.
[0017] By adopting the above technical scheme, the plastic particles are immersed in acetone solution and sodium hypochlorite solution under specific conditions, so that the surface of the plastic particles becomes rough and the structure changes, thereby specially combining with pineapple leaf fiber and chitosan to improve the performance of concrete.
[0018] If the soaking time is too long or too short, or the soaking concentration is too high or too low, or the soaking solvent is changed, the modified plastic particles will not be able to obtain the target structure, and will not be able to cooperate with the pineapple leaf fiber and chitosan, and will not be able to alleviate the problem of plastic floating.
[0019] Preferably, the mineral admixtures include fly ash and mineral powder.
[0020] Preferably, the mineral admixtures are fly ash and mineral powder, and the mass ratio of fly ash to mineral powder is 1:(1-1.5).
[0021] In a second aspect, the present application provides a method for preparing building concrete, which adopts the following technical solution: a method for preparing building concrete, comprising the following steps: mixing all raw materials until uniform to obtain building concrete.
[0022] In summary, this application has the following beneficial effects: 1. Use acetone and sodium hypochlorite to further modify the plastic particles, making the surface of the modified plastic particles rougher and changing the structure of the plastic particles, thereby improving the interface bonding effect with concrete, which is beneficial to the penetration and bonding of cement paste.
[0023] 2. The modified plastic particles cooperate with pineapple leaf fibers and chitosan. The modified plastic particles with special structure can adhere well to the network structure of pineapple leaf fibers. Chitosan, with its good film-forming property and biocompatibility, can promote the close bonding between the network structure and the concrete matrix, so that the network structure can effectively improve the integrity of the concrete.
[0024] 3. The modified plastic particles cooperate with pineapple leaf fibers and chitosan. The modified plastic particles are attached to the pineapple leaf fibers and are "sealed and fixed" by chitosan film formation, which can further effectively alleviate the problem of traditional plastics easily floating.
[0025] 4. When concrete is under pressure, the stable and strong network structure can quickly disperse the stress and alleviate the damage to the concrete caused by pressure. The good deformation effect of the modified plastic particles themselves can further enhance the compressive strength of the concrete. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments.
[0027] The raw materials used in the following examples and comparative examples are all commercially available products. Example
[0028] Example 1 A kind of building concrete comprises the following raw materials: cement, fine aggregate, coarse aggregate, water, mineral admixture, admixture, modified plastic particles, pineapple leaf fiber and chitosan.
[0029] The specific amount of each raw material is shown in Table 1.
[0030] The cement was commercially available P`II 52.5R.
[0031] The fine aggregate is commercially available machine-made sand with grading zone II and fineness modulus of 2.9.
[0032] The coarse aggregate is commercially available granite with a size of 5-25 mm.
[0033] The mineral admixtures are fly ash (grade II) and mineral powder (S95).
[0034] The admixture is commercially available CSP-11 slow-setting high-efficiency water-reducing agent.
[0035] Pineapple leaf fiber was commercially available and purchased from Nuoxiangyuan Agricultural Products Professional Cooperative in Xuwen County.
[0036] Chitosan is commercially available.
[0037] The modified plastic particles are homemade, and the specific preparation includes the following steps: Step a: Acetone and water are mixed in a volume ratio of 4:1 to obtain an acetone solution.
[0038] Commercially available ABS plastic particles (particle size 1-3 mm) were soaked in acetone solution for 1.5 h, and the mass ratio of plastic particles to acetone solution was 1:8.
[0039] The mixture is taken out and dried to constant weight to obtain once-immersed plastic particles.
[0040] Step b: soaking the once-immersed plastic particles in a sodium hypochlorite solution with a mass concentration of 8% for 1.5 hours, and the mass ratio of the once-immersed plastic particles to the sodium hypochlorite solution is 1:4.
[0041] The mixture was taken out and dried to constant weight to obtain modified plastic particles.
[0042] The present application also provides a method for preparing building concrete, comprising the following steps: mixing all raw materials until uniform to obtain building concrete.
[0043] Example 2 A building concrete, which is different from Example 1 in that it includes the following raw materials: cement, fine aggregate, coarse aggregate, water, mineral admixture, admixture, modified plastic particles, pineapple leaf fiber, and chitosan.
[0044] The specific amount of each raw material is shown in Table 1.
[0045] The cement was commercially available P`II 52.5R.
[0046] The fine aggregate is commercially available machine-made sand with grading zone II and fineness modulus of 2.9.
[0047] The coarse aggregate is commercially available granite with a size of 5-25 mm.
[0048] The mineral admixtures are fly ash (grade II) and mineral powder (S95).
[0049] The admixture is commercially available CSP-11 slow-setting high-efficiency water-reducing agent.
[0050] Pineapple leaf fiber was commercially available and purchased from Nuoxiangyuan Agricultural Products Professional Cooperative in Xuwen County.
[0051] Chitosan is commercially available.
[0052] The modified plastic particles are homemade, and the specific preparation includes the following steps: Step a: Acetone and water are mixed in a volume ratio of 3:1 to obtain an acetone solution.
[0053] Commercially available ABS plastic particles (particle size 1-3 mm) were soaked in acetone solution for 2 h, and the mass ratio of plastic particles to acetone solution was 1:5.
[0054] The mixture is taken out and dried to constant weight to obtain once-immersed plastic particles.
[0055] Step b: soaking the once-immersed plastic particles in a sodium hypochlorite solution with a mass concentration of 5% for 2 hours, and the mass ratio of the once-immersed plastic particles to the sodium hypochlorite solution is 1:2.
[0056] The mixture was taken out and dried to constant weight to obtain modified plastic particles.
[0057] The method for preparing a building concrete is the same as that in Example 1 and will not be described in detail herein.
[0058] Example 3 A building concrete, which is different from Example 1 in that it includes the following raw materials: cement, fine aggregate, coarse aggregate, water, mineral admixture, admixture, modified plastic particles, pineapple leaf fiber, and chitosan.
[0059] The specific amount of each raw material is shown in Table 1.
[0060] The cement was commercially available P`II 52.5R.
[0061] The fine aggregate is commercially available machine-made sand with grading zone II and fineness modulus of 2.9.
[0062] The coarse aggregate is commercially available granite with a size of 5-25 mm.
[0063] The mineral admixtures are fly ash (grade II) and mineral powder (S95).
[0064] The admixture is commercially available CSP-11 slow-setting high-efficiency water-reducing agent.
[0065] Pineapple leaf fiber was commercially available and purchased from Nuoxiangyuan Agricultural Products Professional Cooperative in Xuwen County.
[0066] Chitosan is commercially available.
[0067] The modified plastic particles are homemade, and the specific preparation includes the following steps: Step a: Acetone and water are mixed in a volume ratio of 5:1 to obtain an acetone solution.
[0068] Commercially available ABS plastic particles (particle size 1-3 mm) were immersed in an acetone solution for 1 h, and the mass ratio of the plastic particles to the acetone solution was 1:10.
[0069] The mixture is taken out and dried to constant weight to obtain once-immersed plastic particles.
[0070] Step b: soaking the once-immersed plastic particles in a sodium hypochlorite solution with a mass concentration of 10% for 1 hour, and the mass ratio of the once-immersed plastic particles to the sodium hypochlorite solution is 1:5.
[0071] The mixture was taken out and dried to constant weight to obtain modified plastic particles.
[0072] The method for preparing a building concrete is the same as that in Example 1 and will not be described in detail herein.
[0073] Example 4 A building concrete, which is different from Example 1 in that the specific amounts of various raw materials are different, see Table 1 for details.
[0074] Table 1 Example 5 A building concrete, which is different from Example 1 in that the preparation of the modified plastic particles comprises the following steps: Step a: Soak commercially available ABS plastic particles (particle size 1-3 mm) in clean water for 1.5 hours, with the mass ratio of plastic particles to clean water being 1:8.
[0075] The mixture is taken out and dried to constant weight to obtain once-immersed plastic particles.
[0076] Step b: soaking the once-immersed plastic particles in a sodium hypochlorite solution with a mass concentration of 8% for 1.5 hours, and the mass ratio of the once-immersed plastic particles to the sodium hypochlorite solution is 1:4.
[0077] The mixture was taken out and dried to constant weight to obtain modified plastic particles.
[0078] Example 6 A building concrete, which is different from Example 1 in that the preparation of the modified plastic particles comprises the following steps: Step a: Acetone and water are mixed in a volume ratio of 4:1 to obtain an acetone solution.
[0079] Commercially available ABS plastic particles (particle size 1-3 mm) were soaked in acetone solution for 1.5 h, and the mass ratio of plastic particles to acetone solution was 1:8.
[0080] The mixture is taken out and dried to constant weight to obtain once-immersed plastic particles.
[0081] Step b: soaking the once soaked plastic particles in a sodium hydroxide solution with a mass concentration of 8% for 1.5 hours, and the mass ratio of the once soaked plastic particles to the sodium hydroxide solution is 1:4.
[0082] The mixture was taken out and dried to constant weight to obtain modified plastic particles.
[0083] Example 7 A building concrete, which is different from Example 1 in that the preparation of the modified plastic particles comprises the following steps: Step a: soak commercially available ABS plastic particles (particle size 1-3 mm) in a sodium hypochlorite solution with a mass concentration of 8% for 1.5 hours, and the mass ratio of the plastic particles to the sodium hypochlorite solution is 1:4.
[0084] The mixture is taken out and dried to constant weight to obtain once-immersed plastic particles.
[0085] Step b: Acetone and water are mixed in a volume ratio of 4:1 to obtain an acetone solution.
[0086] The plastic particles were immersed in the acetone solution for 1.5 hours, and the mass ratio of the plastic particles to the acetone solution was 1:8.
[0087] The mixture was taken out and dried to constant weight to obtain modified plastic particles.
[0088] Comparative Example Comparative Example 1 A building concrete, which is different from Example 1 in that the modified plastic particles are replaced by commercially available ABS plastic particles.
[0089] Comparative Example 2 A building concrete, which is different from Example 1 in that the pineapple leaf fiber is replaced by steel fiber.
[0090] Comparative Example 3 A building concrete, which is different from Example 1 in that chitosan is replaced by xanthan gum.
[0091] Comparative Example 4 A building concrete, which is different from Example 1 in that the pineapple leaf fiber is 3.5 kg and the chitosan is 8 kg.
[0092] Performance testing 1. Compressive strength: Referring to GBT 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 28d compressive strength test was performed on the building concrete of Examples 1-7 and Comparative Examples 1-4, and the compressive strength was recorded in Table 2.
[0093] 2. Split tensile strength: Referring to GBT 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the building concrete of Examples 1-7 and Comparative Examples 1-4 was subjected to a 28d splitting tensile test, and the splitting tensile strength was recorded in Table 2.
[0094] 3. Chloride ion penetration resistance: Referring to GB / T 50082-2009 "Standard for test methods for long-term performance and durability of ordinary concrete", the building concrete of Examples 1-7 and Comparative Examples 1-4 was tested for chloride ion penetration resistance, and the chloride ion penetration depth was recorded in Table 2.
[0095] Table 2 Comparative Examples 1-3 are based on Example 1, and any of the modified plastic particles, pineapple leaf fiber, and chitosan are replaced with other raw materials; Comparative Example 4 is based on Example 1, and the dosage matching relationship of the modified plastic particles, pineapple leaf fiber, and chitosan in the system is destroyed. According to the test data of Table 2, the compressive strength and splitting tensile strength of the concrete obtained by Comparative Examples 1-4 are significantly lower than those of Example 1, and the penetration degree of chloride ions is also more serious. It is explained that when the modified plastic particles, pineapple leaf fiber, and chitosan act in the concrete under specific conditions, the problems such as the easy floating of plastics and the poor performance of concrete strength can be improved. The special matching between modified plastic particles, pineapple leaf fiber, and chitosan cannot play a matching role if the special relationship is replaced or destroyed at will, so that the performance is greatly reduced.
[0096] Embodiment 5-7 is based on embodiment 1, and the means of modifying plastic particles is changed. According to the test data of Table 2, compared with embodiment 1, embodiment 5-7 has different degrees of decline in compressive strength and splitting tensile strength, and the penetration ability of chloride ions is also stronger. It is explained that if the raw materials used for modifying plastic particles can be further limited, the modified plastic particles can have a special structure, and can have a more sufficient coordination effect with pineapple leaf fiber and chitosan. If the modified raw materials are changed, although the surface of the modified plastic particles can be made rough to a certain extent, it is impossible to have the best coordination effect with pineapple leaf fiber and chitosan.
[0097] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A building concrete, characterized in that: According to the mass proportion, the raw materials include: 220-240 parts of cement, 690-715 parts of fine aggregate, 1050-1150 parts of coarse aggregate, 130-150 parts of water, 140-170 parts of mineral admixture, 5-10 parts of admixture, 10-30 parts of modified plastic particles, 5-10 parts of pineapple leaf fiber, and 1-5 parts of chitosan; The modified plastic particles are prepared by modifying plastic particles with acetone and sodium hypochlorite.
2. The construction concrete according to claim 1, characterized in that: In terms of weight percentage, the modified plastic particles account for 15-25 parts, the pineapple leaf fibers account for 6.5-8 parts, and the chitosan accounts for 1.5-3.5 parts.
3. The construction concrete according to claim 1, characterized in that: The preparation method of the modified plastic particles comprises the following steps: Step a: soaking the plastic particles in an acetone solution, taking them out and drying them to obtain once-soaked plastic particles; Step b: soaking the once-immersed plastic particles in a sodium hypochlorite solution with a mass concentration of 5-10% for 1-2 hours, and the mass ratio of the once-immersed plastic particles to the sodium hypochlorite solution is 1: (2-5); taking out and drying to obtain modified plastic particles.
4. The construction concrete according to claim 3, characterized in that: The acetone solution is a mixture of acetone and water in a volume ratio of (3-5):
1.
5. The construction concrete according to claim 4, characterized in that: The mass ratio of the plastic particles to the acetone solution is 1:(5-10).
6. The construction concrete according to claim 3, characterized in that: In the step a, the plastic particles are immersed in the acetone solution for 1-2 hours.
7. The construction concrete according to claim 1, characterized in that: The mineral admixtures include fly ash and mineral powder.
8. The construction concrete according to claim 7, characterized in that: The mineral admixtures are fly ash and mineral powder, and the mass ratio of fly ash to mineral powder is 1: (1-1.5).
9. A method for preparing building concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: All the raw materials are mixed until uniform to obtain concrete for construction.